Solve a Trigonometric Equation!

Geometry Level 4

2 1 + 3 cos x 10 2 1 + 2 cos x + 2 2 + cos x 1 = 0 \large 2^{1+3\cos x} - 10 \cdot 2^{-1+2\cos x} + 2^{2+\cos x} - 1 = 0

If x x in the interval 0 x < 2 π 0 \leq x < 2 \pi , find the sum of all possible values of x x satisfying the equation above.

Give your answer to 2 decimal places.


The answer is 9.42.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Rishabh Jain
May 12, 2016

Using elementary rules of exponentials write equation as: 2 ( 2 cos x ) 3 5 ( 2 cos x ) 2 + 4 ( 2 cos x ) 1 = 0 2(\color{#3D99F6}{2^{\cos x}})^3-5(\color{#3D99F6}{2^{\cos x}})^2+4(\color{#3D99F6}{2^{\cos x}})-1=0 This is a trivial cubic equation, substitute t = 2 cos x \color{#3D99F6}{t=2^{\cos x}} .

2 t 3 5 t 2 + 4 t 1 = 0 \large 2\color{#3D99F6}{t}^3-5\color{#3D99F6}{t}^2+4\color{#3D99F6}{t}-1=0

( t 1 ) 2 ( 2 t 1 ) = 0 t = 2 0 , 2 1 \large \implies (\color{#3D99F6}{t}-1)^2(2\color{#3D99F6}{t}-1)=0\implies t=2^0,2^{-1}

cos x = 0 , 1 \large \implies \cos x=\color{#D61F06}{0},\color{#20A900}{-1}

x = 3 π 2 , π 2 , π \large \implies x=\color{#D61F06}{\dfrac{3\pi}{2},\dfrac{\pi}{2}},\color{#20A900}{\pi} Their sum = 3 π 9.42 \large\text{Their sum}=3\pi\huge \approx \boxed{9.42}

nice solution .. +1

Sabhrant Sachan - 5 years, 1 month ago

Log in to reply

T h a n k s ! ! \large\mathcal{T}hanks!!

Rishabh Jain - 5 years, 1 month ago

T o o k 1 2 π i n s t e a d o f 3 2 π ! ! Took\ \ \ \ - \frac 12 *\pi \ \ instead \ \ of\ \ \frac 3 2 *\pi \ \ \ \ !!

Niranjan Khanderia - 5 years ago
Chew-Seong Cheong
May 12, 2016

2 1 + 3 cos x 10 2 1 + 2 cos x + 2 2 + cos x 1 = 0 Let y = 2 cos x 2 y 3 5 y 2 + 4 y 1 = 0 ( y 1 ) 2 ( 2 y 1 ) = 0 y = { 1 1 2 2 cos x = { 2 0 2 1 cos x = { 0 1 x = { π 2 , 3 π 2 π \begin{aligned} 2^{1+3\cos x} - 10 \cdot 2^{-1+2 \cos x} + 2^{2+\cos x} - 1 & = 0 \quad \quad \small \color{#3D99F6}{\text{Let }y = 2^{\cos x}} \\ \implies 2y^3 - 5y^2 +4y - 1& = 0 \\ (y-1)^2(2y - 1) & = 0 \\ \implies y & = \begin{cases} 1 \\ \frac{1}{2} \end{cases} \\ 2^{\cos x} & = \begin{cases} 2^0 \\ 2^{-1} \end{cases} \\ \cos x & = \begin{cases} 0 \\ -1 \end{cases} \\ \implies x & = \begin{cases} \frac{\pi}{2}, \ \frac{3\pi}{2} \\ \pi \end{cases} \end{aligned}

The sum of x x satisfying the equation is π 2 + 3 π 2 + π = 3 π 9.42 \dfrac{\pi}{2} + \dfrac{3\pi}{2} + \pi = 3 \pi \approx \boxed{9.42} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...